Developing a Video-Based Self-Assessment Model for Speaking Skills of High School English Language Learners. - To'raboyeva Xumora; Mukhabbat Anatolevna Yusupova (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This study explores the development and implementation of a video-based self-assessment model designed to enhance speaking skills among high school English language learners (ELLs), with a particular focus on the context of Uzbekistan. The model integrates video recording technology to allow students to review their oral performances, identify strengths and weaknesses, and set personal improvement goals. Drawing on principles of self-regulated learning and formative assessment, the research involved 120 high school students from grades 9-11 in Tashkent, Uzbekistan. Participants engaged in structured speaking tasks, recorded their performances, and used a self-assessment rubric to evaluate aspects such as pronunciation, fluency, vocabulary, and non-verbal communication. Pre- and post-intervention assessments revealed significant improvements in speaking proficiency, self-efficacy, and motivation. The findings indicate that video-based self-assessment not only boosts linguistic competence but also fosters learner autonomy, addressing common challenges in English language education in non-native contexts. This model offers practical implications for educators seeking innovative, technology-integrated approaches to speaking skill development.